Hands-Only Cardiopulmonary Resuscitation Education for Elementary School Students in Korea: Tracking by School Grade, Physical Characteristics, and Physical Strength - Jang Sik Ko; Seon Rye Kim; Byung Jun Cho (Frontiers Media S.A., 2024)
Objectives: This study aimed to assess variations in chest compression depth among Korean elementary school students based on grade, physical characteristics, and strength.Methods: The study involved 140 children in the third to sixth grades from elementary schools. Before providing cardiopulmonary resuscitation (CPR) education, we assessed height, weight, BMI, grip strength, and back strength. Subsequently, CPR education was administered, followed by individual measurements of compression depth. The factors related to compression depths was analyzed using t-test, ANOVA and multivariable regression.Results: The mean compression depth was consistently lower than the guideline standard across all grades, indicating grade-dependent differences (p = 0.000). Moreover, height, weight, BMI, grip strength and back strength increased, exhibited significant increases with grade (p = 0.000). In multivariable regression analysis, it was observed that as grade increased, chest compression depth increased by 0.701 cm (p = 0.000).Conclusion: School grade significantly influenced achieving the proper chest compressions depth, no notable correlation found for physical factors. Thus, a strategy emphasizing the importance of sufficient chest compressions during CPR education, particularly targeting elementary school students, seems necessary to encourage greater effort.